Misclassification of Self‐Directed Violence. (2nd August 2016) - Cwik, Jan Christopher; Teismann, Tobias
Abstract : Background: Inconsistent nomenclature and classification of suicidal behaviour have plagued the field of suicidology for a long time. Recently, the United States Centers for Disease Control (CDC) advocated for the usage of a specific classification system. Aim of the current study was to determine the extent of misdiagnosed acts of self‐directed violence—controlling for the level of expertise in psychology/psychotherapy. Additionally, the effect of gender and diagnosis on misclassifications was assessed. Method: A total of 426 participants (laypersons, psychology students, psychotherapists‐in‐training, licensed psychotherapists) were presented with an array of case vignettes describing different acts of self‐directed violence (e.g., non‐suicidal self‐directed violence, suicide attempt, suicide ideation) and were asked to make a classification. Gender and given diagnosis were varied systematically in two vignettes. Results: Overall 51.6% of the cases were misclassified (according to the Self‐Directed Violence Classification System). The level of expertise was almost unrelated to classification correctness. Yet, psychotherapists were more confident about their judgments. Female gender of the character described in the vignette and an ascribed diagnosis of Borderline Personality Disorder were associated with higher misclassification rates. Limitations: The validity of case vignettes is discussible. Conclusions: The results highlight the importance of more methodological and diagnostic training of psychologists regarding suicidal issues. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioner Message: Misclassification of non‐suicidal and suicidal events is common. Expertise is only weakly associated with classification correctness. Misclassification of suicide attempts occurs more often in women. Misclassification of suicide attempts occurs more often in Borderline Personality Disorder. The use of standardized diagnostic tools in relation to self-directed violence is highly recommended.